Prototype Instrumentation for the Spatial and Temporal Characterisation of Voltage Supply Based on Two-Dimensional Higher-Order Statistics - Juan-José González-de-la-Rosa; Olivia Florencias-Oliveros; José-María Sierra-Fernández; Manuel-Jesús Espinosa-Gavira; Agustín Agüera-Pérez; José-Carlos Palomares-Salas; Victor Pallarés-López; Rafael-Jesús Real-Calvo; Isabel Santiago-Chiquero (Energies)
This paper presents a proof-of-concept of a versatile Power Quality (PQ) analyser for tracking the voltage supply in industrial and residential sectors. It implements 2D Higher-Order Statistics (HOS) to assess voltage quality, based more on the sinusoidal waveform than on power fluctuations. Beyond the second-order parameters and permissible deviations regulated by the norm, EN 50160, the two-dimensional traces and probability density functions, along with a previously studied differential index, manage to identify different states of the electrical grid. Waveforms were measured in the wall plugs of a public building. In regard to analysing reliability and voltage waveform, the results corroborate that incorporating skewness and kurtosis indicators improves the characterisation, as well as extracting the customers’ supply behaviour under normal and anomalous operations. The instrument showed good behaviour in site characterisation, and the implemented method was considered as a probabilistic approach for the risk assessment of an installation. The prototype was tested in the facilities of a public building of the university, being able to detect deviations in 10 s traces of 3.9% in variance and 0.6% in kurtosis.